Creditor rights and capital structure: Evidence from international data - Cho, Seong-Soon; El Ghoul, Sadok; Guedhami, Omrane; Suh, Jungwon (Journal of Corporate Finance, 2014)
For a large sample of 48 countries, we find robust evidence that strong creditor rights are associated with low long-term leverage across countries. We further find that strong creditor protection lowers long-term debt issuance, the extent to which investments are financed with long-term debt, and target leverage ratios. Finally, we find that firm and country characteristics influence the link between creditor protection and long-term leverage. Our results support the demand-side view that strong creditor protection discourages firms from making long-term cash flow commitments to service debt because managers and shareholders avoid the risk of losing control in the case of financial distress.